Analisis Kesalahan Berbahasa pada Berita Seputar Sekolah dalam Majalah OBAH SMAN 1 Balapulang sebagai Sumber Bacaan Siswa - Allyssa Ramadhani; Na’ila Sarwahita; Refa Amelia Putri; Aufannida Rahmalika Salsa Billa Azizia; Rina Mayaningsih; Agustin Kusumawardani; Asep Purwo Yudi Utomo; Riskiana Widi Astuti (BADAN PENERBIT STIEPARI PRESS, 2025)
Language, as defined by Kridalaksana and Depdikbud, is a system of arbitrary sound symbols used by members of a society to cooperate and interact. The main aspects of language include human nature, learnability, systematic structure, arbitrariness, and symbolic function. Language distinguishes humans from other creatures, facilitating the communication of thoughts and feelings. Language learning is a gradual process influenced by the environment, such as school, home, and the circle of friends. The language system consists of grammatical rules that ensure structured communication. Errors in language arise from systematic difficulties with grammar. This study analyzes language errors found in news articles in OBAH Magazine, focusing on spelling errors, including capitalization, italics, prepositions, use of affixes, word division, writing of loan words, and punctuation. Clear and accurate language is essential in the media, especially school magazines such as OBAH. Identifying these problems can improve students' understanding of the information conveyed. This study addresses the research gap regarding language errors in a particular school magazine, which contributes to improving the quality of language in educational contexts. The qualitative method emphasizes understanding social phenomena, utilizing observation, interviews, and documentation for data collection. The analysis involves categorizing and reconstructing data to offer recommendations for improving students' critical reading and literacy skills, which ultimately helps their social communication skills.